Studi Perbandingan Tingkat Resiliensi Pengguna Narkoba Ditinjau Berdasarkan Tingkat Usia - Farial Farial; Eka Sri Handayani; Sabit Tohari (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2020)
The various problems and difficulties faced by prisoners are challenges that must be faced in serving a sentence. Efforts in overcoming changes and challenges faced by prisoners are closely related to resilience. Resilience is the ability of individuals to deal with conditions of difficulty or suffering (Connor & Davidson, 2003). Quantitative research methods in this study use comparative research. According to Silalahi Ulber (2005) comparative research is research that compares two or more symptoms. Comparative research can be in the form of descriptive comparative (descriptive comparative) or correlative comparative (correlation comparative). In this study, researchers wanted to compare the level of drug user resilience reviewed based on the age level of women fostered citizens in Lapas II A Martapura. Research Results Respondents used in this study were 110 Former Citizens of Former Drug Users in Class II A Women's Prison in Martapura, with details as follows from 110 assisted residents, as many as 36 (32.7%) are inmates aged 40 - 65 years, and 74 (67.3%) are inmates under the age of 40 years. Based on data analysis that has been done using Pearson Product Moment analysis, obtained a coefficient (r) of 0.195 with a significance value (p) of 0.041 <0.05, this shows that there is a positive relationship between age and resilience ability. From the results of data analysis, the coefficient of variable determination (r2) was 0.038 (3.8%). This shows that the effect of age on increasing resilience ability is 3.8%, and the remaining 96.2% is influenced by other factors. Keywords: Resilience, Drug Users, Assisted Residents